The Power of Belief: How Self-Efficacy Shapes Teacher Readiness through Technological Pedagogical Content Knowledge-Based Dynamic Capabilities - Aldila Krisnaresanti; Suwatno; Hari Mulyadi; Dian Herdiana Utama (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
In the digital transformation era, differentiated learning is an important strategy for addressing diverse students’ needs. This study examines the influence of teacher self-efficacy on readiness to implement differentiated learning and the mediating role of Technological, Pedagogical, and Content Knowledge (TPACK)-based Dynamic Capability. Using a quantitative approach and a survey of 73 economics teachers in Islamic high schools in Central Java, Indonesia, the data were analyzed using PLS-SEM. The results show that self-efficacy does not directly affect teacher readiness. However, self-efficacy significantly affects TPACK-based dynamic capability, which in turn significantly affects teacher readiness. The indirect mediation effect of TPACK-based dynamic capability reinforces the importance of adaptive professional capacity in e-learning integration. The main scientific contribution of this study is the introduction of a new construct, namely TPACK-based Dynamic Capability, which combines psychological theory (self-efficacy) with the TPACK framework through a dynamic capability perspective. This construct represents teachers’ ability to adaptively integrate technological, pedagogical, and content knowledge in changing contexts. The practical implication is that teacher professional development programs must emphasize increasing self-efficacy and TPACK-based adaptive skills to create effective differentiated learning in the digital era.